COMPARISON OF MULTIMODAL ANALGESIA FOR PAIN CONTROL AND MEASURING INFLAMMATION LEVELS USING PARACETAMOL WITH VARIOUS DOSAGE OF IBUPROPHENE IN CAESARIAN SURGICAL PATIENTS - Yudhitya Afif; Syafruddin Gaus; Alamsyah Ambo (Universitas Islam Negeri Alauddin Makassar, 2022)
The concept of multimodal analgesia in the treatment of postoperative pain has been around for a long time. Various drugs have been used to control pain after cesarean section (SC). The purpose of this study was to compare the combination of paracetamol with ibuprofen at various doses as multimodal analgesia and to measure levels of Interleukin-6 (IL-6) as a marker of inflammation in CS surgical patients. Methods this study was a single-blind experimental study. A total of 40 patients who underwent SC surgery under spinal anesthesia using hyperbaric Bupivacaine 0.5% 8 mg were divided into 2 groups, namely IBU4 group (paracetamol 750 mg and ibuprofen 400 mg), and IBU8 (paracetamol 750 mg and ibuprofen 800 mg) given intravenously 1 hour preoperatively, and every 6 hours for 24 hours. Then the degree of pain was assessed at rest and moving using a Numeric Rating Score (NRS) at 2, 4, 6, 12, and 24 hours postoperatively, and IL-6 levels were measured 1 hour preoperatively, 6 and 12 hours postoperatively. Calculate the amount of fentanyl given for rescue. Then repeated ANOVA, paired t-test, and chi-square analysis were performed using SPSS 21 for Windows. The results are declared meaningful if the p-value < 0.05. The results the IBU8 group showed lower values of the silent NRS, motion NRS, and IL-6 levels than the IBU4 group; this difference was significant with a value (p<0.05). All patients in the IBU8 group also did not require rescue fentanyl (p<0.05). The combination of paracetamol 750 mg and ibuprofen 800 mg showed the best results on NRS values, IL-6, and CRP levels for postoperative pain management SC without the need for rescue fentanyl and side effects.